If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 7 = -4y + 5 Reorder the terms: 7 + -3y = -4y + 5 Reorder the terms: 7 + -3y = 5 + -4y Solving 7 + -3y = 5 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 7 + -3y + 4y = 5 + -4y + 4y Combine like terms: -3y + 4y = 1y 7 + 1y = 5 + -4y + 4y Combine like terms: -4y + 4y = 0 7 + 1y = 5 + 0 7 + 1y = 5 Add '-7' to each side of the equation. 7 + -7 + 1y = 5 + -7 Combine like terms: 7 + -7 = 0 0 + 1y = 5 + -7 1y = 5 + -7 Combine like terms: 5 + -7 = -2 1y = -2 Divide each side by '1'. y = -2 Simplifying y = -2
| -12=5x-9x-24 | | 4=3x+12 | | x^6=140 | | 2x+11=7x+6 | | x-4=2y+5 | | 80+1.6x= | | -3a+2+4a=14-21 | | -7(k+9)-(-9k-9)=k | | 7x-5=6x+3 | | -4(4-3y)=3y+29 | | -3r-4(r+3)=3 | | 0=x-(0.04*x^2) | | -13=4P-1 | | 6+2x=33minusx | | -5=7-(10-b) | | -3a+7=1 | | -2d+3=17+9d | | 5=4r(2r+3) | | 2(2x+2)=3(x-5) | | 4+8(t-7)=4(t+1)+4 | | -5(2x-6)=5x | | 18+5y=7y-12 | | (4x+20)=(2x+60) | | 9x-10=3x+2 | | (4x+20)+(2x+60)=180 | | X^2-11x+19=0 | | x+x+x=33 | | (5x+40)+2x=180 | | 4x-8=2-x | | X-6=-x^2 | | Z-8z=6z-7-z | | 2(3a^2-1)-6a=5a |